2006
DOI: 10.1002/nme.1888
|View full text |Cite
|
Sign up to set email alerts
|

Analytical integrations and SIFs computation in 2D fracture mechanics

Abstract: SUMMARYAnalytical integrations, in the framework of linear elastic problems modelled by means of boundary integral equations, have been considered in a previous publication (Int. J. Numer. Methods Eng. 2002; 53(7):1695-1719): the present note aims at extending the subject to linear elastic fracture mechanics. In such a context, special shape functions have been recently proposed (SIAM J. Appl. Math. 1998; 58: 428-455) in order to increase accuracy in stress intensity factors approximation: the closed form solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…[42]. Indeed, closed forms (44), (51), (52) and (61) allow the extension to 3D fracture mechanics of the important result of Gray and Paulino [43]: in a nutshell, it has been shown that-as it happens in two dimensions-the linear term of the expansion of crack opening and sliding about the crack tip vanishes.…”
Section: Final Remarksmentioning
confidence: 97%
“…[42]. Indeed, closed forms (44), (51), (52) and (61) allow the extension to 3D fracture mechanics of the important result of Gray and Paulino [43]: in a nutshell, it has been shown that-as it happens in two dimensions-the linear term of the expansion of crack opening and sliding about the crack tip vanishes.…”
Section: Final Remarksmentioning
confidence: 97%
“…[1]. Let * = p + u + + w + − w denote the 'real' boundary of and = p + u + w its idealization: assume to be a piecewise smooth curve in R 2 .…”
Section: Motivationsmentioning
confidence: 99%
“…In the small displacement and strains hypothesis, consider the response of B to the following quasi-static actions: tractionsp(x) on p , displacementsū(x) on u along the boundary, zero bulk forces in . The problem stated above will be termed linear elastic fracture mechanics (LEFM) problem and its numerical approximation is addressed in [1]. In such a framework, the present note aims at studying the approximation of stress vector p(x, n(x)) acting at point x ∈ on a surface of normal n(x).…”
Section: Motivationsmentioning
confidence: 99%
See 2 more Smart Citations